Cartographic modelling of administrative divisions in the “Historical Atlas of Poland” - Panecki Tomasz (Polish Cartographical Review, 2020)
The author’s aim is to reflect on the cartographic modelling of historical borders based on the example of the series “Historical Atlas of Poland. Detailed maps of the 16th century” (HAP). HAP presents secular (state, palatinate, district) and religious borders (dioceses, archdeaconry, deanery, parish). The belonging of historic settlements to administrative units is determined on the basis of written sources. During work on the current volumes of HAP, the borders were reconstructed through their manual interpolation (the so-called linear model). Digital tools enable the automatic generation of administrative units based on settlements in point geometry (Thiessen polygons) or the use of modern divisions (precincts [obręby ewidencyjne]) as a reference to them (semi-automatic method). The article compares and assesses the three mentioned methods of determining historical borders and the possibilities of harmonizing them in relation to contemporary administrative divisions. The source material consisted of 18,357 settlements from the volumes of HAP published so far and 235 parishes for detailed analyses. Precincts were adopted as reference areas due to the possibilities of data harmonization.